Striking the balance : debating criminal justice and law - Lippman, Matthew Ross, 1948- (Los Angeles, CA : SAGE Publications, Inc., 2018)
KEY FEATURES A brief introduction to the U.S. judicial system and to the public policy dimension of judicial decisions provides context for the material. Criminal and regulatory laws are presented with contrasting views on various contemporary public policy issues, including assault weapons, hate crimes, stand your ground laws, police use of deadly force, and much more. A question for debate and learning objectives appear at the beginning of each chapter. The debate format features contemporary topical issues that engage students and ask them to consider various points of view. Brief essays introduce students to each debate and put the issue into context to help students understand how policy issues arise in criminal justice and law. Summaries of the positions follow the debate sections to ensure students have a clear understanding of the contrasting arguments. 'You Decide' exercises and discussion questions appear at the end of each debate to give students the opportunity to apply what they read to new and novel situations.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Criminal justice, Administration of -- United States; Criminal law -- United States; United States; Punishment -- United States